Analysis of the Environmental Health Risks of Lead (Pb) Pollution in Well Water around the Pakusari Jember Landfills - Lisa Nourma Junita; Ady Soesetijo; Isa Ma’rufi (Aloha International Journal of Health Advancement (AIJHA), 2019)
Continuous landfilling in the Pakusari Jember landfills will produce pollutants in the form of leachate which is very risky to pollute well water belonging to residents living near the Pakusari Jember landfills. This study aims to analyze the environmental health risks of lead pollution (Pb) in well water around the Pakusari Jember landfills. This research was a descriptive study with a research design using the Environmental Health Risk Analysis method. People sample in this study were 64 people who were respondents to calculate the risk of respondents exposed to lead (Pb). The well water sample were 23 wells. The concentration of lead (Pb) in the well water of the population was analyzed using Atomic Absorption Spectrophotometer (AAS), while the body weight, intake rate, exposure frequency, and duration of exposure were obtained from interviews with 64 respondents to calculate (I) lead (Pb) and the level of health risk (RQ). The results showed that the average value of lead concentration (Pb) in the resident well water around the Pakusari Jember landfills was 0.058 mg/L. The results of the calculation of the maximum risk level (RQ) in the population is 2, this indicates that lead exposure (Pb) has a risk of health problems because of the value of RQ>1. If the value of risk level (RQ)>1, risk management is needed . Keywords: risk analysis; lead (Pb); landfills